PD-L1 expression and clinical outcomes in patients with advanced urothelial carcinoma treated with checkpoint inhibitors: A meta-analysis. (June 2019) - Ghate, Ketan; Amir, Eitan; Kuksis, Markus; Hernandez-Barajas, David; Rodriguez-Romo, Laura; Booth, Christopher M.; Vera-Badillo, Francisco E.
Highlights: Checkpoint inhibitors impact survival of patients with urothelial carcinoma. Long term responses to checkpoint inhibitors are now seen. Unfortunately, only 30% of patients get this benefit. Patient selection utilizing biomarkers that are prognostic of response is critical. Abstract: Context: Five checkpoint inhibitors have been approved as 1st line (cisplatin-ineligible) or 2nd line therapies for patients with metastatic urothelial carcinoma of the bladder. As only about 30% of patients respond, the need for a biomarker for patient selection exists. Objective: To determine if PD-L1 expression is a prognostic factor of objective response rate (ORR) and overall survival (OS) in patients with urothelial carcinoma being treated with checkpoint inhibitors. Evidence acquisition: A search of PubMed and major conference proceedings identified trials of PD-L1 inhibitors as first- or second-line therapies for metastatic bladder cancer. Odds ratios (OR) for ORR and OS compared PD-L1 positive and PD-L1 negative patients. Data were weighted and pooled in a meta-analysis, and subgroup analyses compared PD-L1 status cut-offs. Evidence synthesis: Ten studies comprising 2755 patients were identified, of which 2030 patients (74%) received immune checkpoint inhibitors. Eight studies were eligible for ORR analysis (1530 patients) and five studies for OS (829 patients). PD-L1 patients had a significantly higher ORR than PD-L1 negative patients (1.82, 95%CI 1.18–2.77; p = 0.007). Weighted mean OS was 11.5 months (range 8.7–15.9 months). PD-L1 status was not prognostic for 12 month OS (OR = 0.81, 95%CI 0.47–1.40; p = 0.45). Conclusion: In patients treated with PD-L1 inhibitors for metastatic urothelial carcinoma, PD-L1 status is prognostic for ORR but not OS. Our findings warrant additional investigation. Patient summary: Five immunotherapy drugs are approved for bladder cancer therapy. PD-L1 expression predicts higher ORR but not OS. More data is needed to identify the patient population most benefitted by immunotherapy.